PENINGKATAN HASIL BELAJAR IPS MELALUI METODE TWO STAY TWO STRAY PADA SISWA KELAS V SDN CEMPAKA BARU 01 JAKARTA PUSAT - Friska Nur Prihati; Ati Kusmawati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTThis study entitled “Peningkatan Hasil Belajar IPS Melalui Metode Two Stay Two Straypada Siswa Kelas V SDN Cempaka Baru 01 Jakarta Pusat”. The subject of this researchis the grade V. This study departs from the background of the results of the study subjectsare still low, IPS under KKM. So author moved to find the cause and try to improve thelearning outcomes through learning methods two stay two stray (tsts). As for the purposeof this research is to improve the learning outcomes of students of class V SDN CempakaBaru 01 on social science subjects.The method used is the class action Research withtwo cycles of hypothesis method with two stay two stray can improve the learning resultsof IPS on grade V in SDN Cempaka Baru 01. The results showed that the method canimprove the learning results of tsts cognitive, affective and psychomotor the students insocial science subjects. The results of the student learning experience an increase inclassical and individually. This is due to the use of cooperative learning model of typetwo stay two stray has involved students learn actively and enhance their understandingof the material being taught. In Cycle I, students who complete of 44.83%, cycle II of93.10%. While in the realm of affective in cycle I are classical space being in thecategory is good enough and in cycle II are in the category either. And in the realm ofpsychomotor, in classical average cycle I showed enough skilled category and on cycleII shows the category of skilled.Keywords: two stay two stray, the results of the study, IPS.